Governing complexity: polycentricity and customary property rights in the commons - Carlisle, Keith M., author; Gruby, Rebecca L., advisor; Basurto, Xavier, committee member; Fernandez-Gimenez, Maria, committee member; Gavin, Michael, committee member (Colorado State University. Libraries, 2018)
Broadly, this dissertation research examines natural resources governance approaches that may facilitate the achievement of desirable social and ecological outcomes. It takes, as its point of departure, a nearly half-century-old concept that is experiencing a renaissance among natural resources governance scholars: polycentricity, a complex and multilevel form of governance comprised of a plurality of semi-autonomous decision makers. Despite its age and apparent popularity, the concept of polycentricity remains conceptually fuzzy and empirically underdeveloped in the commons. This dissertation addresses these deficiencies through conceptual and empirical contributions to the growing scholarship on polycentricity. In its conceptual contribution, this dissertation develops a theoretical model of a functional polycentric governance system for natural resources governance. For this purpose, "functional" refers to the capacity of the governance system to exhibit particular advantages that are commonly attributed to polycentric governance systems by scholars. In doing so, it builds greater clarity around the concept and the conditions under which it may lead to predicted or desired outcomes. This dissertation then examines the functioning of a polycentric governance system through a qualitative case study of small-scale fishery governance in the Northern Reef region of the Republic of Palau, a small island nation in the western Pacific. Deficiencies in institutional features are identified that partly explain why the governance system does not fully achieve the advantages commonly attributed to polycentric governance systems. In addition, analysis of the historical transition of the governance system from community based to polycentric reveals that the path to polycentricity, the particular form of polycentricity, and contextual conditions constitute additional distal explanations of deficiencies in functionality. The case underscores the need for more refined theory concerning the emergence and functionality of different forms of polycentricity in various contexts. In its empirical contributions, this dissertation also speaks to small-scale fishery policy through a finer-scale examination of the social function of customary marine tenure institutions in the Northern Reef state of Ngarchelong. These informal institutions define, among other things, eligibility criteria for those having a recognized right to fish in the state. Flexible administration of customary marine tenure institutions enables Ngarchelong residents to secure material support from nonresident community members and also strengthens social bonds and networks as the community becomes more dispersed in Palau. This research calls attention to the possible social impacts of fishery policies that redefine or formalize fishery access and use rights, and it describes a general approach for better harmonizing fishery policy with local social context and customary institutions.